Screening of Antibiofilm Activity from Marine Bacteria against Pathogenic Bacteria - ALIANDA BUDHIRIANi ROSSATI CAMESI; AGUSTINA LUKITO; DIANA ELIZABETH WATURANGI; HWANG JAE KWAN (Microbiology Indonesia, 2016)
Bacterial biofilms produced by pathogenic bacteria have become a serious issue in several chronic diseases such as atherosclerosis, cystic fibrosis, endocarditis, inner ear infections, and kidney stones. Thus, inhibition and destruction of bacterial biofilm from pathogenic bacteria is needed. The purpose of this study is to analyze biofilm inhibition and destruction activities of marine bacteria associated with hard and soft corals isolated from several oceanic regions in Indonesia. Fifteen marine isolates collected from several regions in Indonesia such as Bali Province, South East Sulawesi Province, East Java Province, Lampung Province, and Banten Province were tested using static biofilm assay against several pathogenic bacteria. Biofilm of the pathogenic bacteria tested were stained using 0.4% crystal violet. Several isolates were sequenced using 16S rRNA PCR method. Most of marine isolates presented higher inhibition and or destruction activity at 10% crude concentration. Few isolates were further identified using 16S rRNA and proven to have antibiofilm activity against several pathogenic bacteria. Marine bacteria have broad applications in medical and pharmaceutical industries and the oceanic regions of Indonesia are promising sources for the discovery of novel bacteria with antibiofilm activity.